Implementation of Humanism Learning in Learning Islamic Religious Education in the Modern Era - Ridwan, Muhammad; Lalu Agus Satriawan (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
The purpose of writing this work is to analyze the challenges of the modern era for Islamic religious learning and the implementation of humanism learning. Literature review as an effective approach in collecting, analyzing, and synthesizing information related to the implementation of humanism learning in Islamic religious education in the modern era. With systematic steps, this research allows the identification of relevant humanism principles, strategies, benefits, and challenges. The results of this literature review research provide a deep understanding and an important contribution to the development of Islamic religious education following the demands of the times. This method also offers a strong theoretical foundation for understanding the relationship between humanism and Islamic education. The result of this research is that Islamic learning in the modern era is faced with complex challenges such as the integration of technology with religious values and contextual understanding in a multicultural environment. Solutions that can be applied include developing an online learning platform that pays attention to religious values and prioritizes inclusive interfaith understanding. Strengthening the religious-based character of education and integrating Islamic religious studies with other subjects in an interdisciplinary attitude is also important in answering this challenge. The implementation of humanism learning can form inclusive, empowered, and noble generation learning in Islamic religious education, but challenges such as the integration of humanist values with religious teachings and improving the quality of education need to be overcome to succeed.